ANALISIS STRUKTUR GEOLOGI DAERAH LEATO SELATAN DAN SEKITARNYA, KECAMATAN DUMBO RAYA, KOTA GORONTALO - Ratna Sari Madusila; Nurhajidah Muhsin; Intan Noviantari Manyoe; Ivan Taslim; Emi Prasetyawati Umar; Anggun Farwati Abdullah; Fauzul Chaidir A. Usman (Universitas Tamansiswa Padang, 2020)
The research area is located in South Leato, Dumbo Raya District, Gorontalo City. The research area is consist of Bone Diorite Formation which is in the miocene and the Pinogu Volcano Rock Formation which is in the quarter. The geological structure of the study area recorded in different rock formations is very interesting to be studied. The purpose of this study is to identify the types and general directions of geological structures that control the stress regime in the study area. This research method is in the form of field data collection and studio analysis. Data is collected by the field survey method. Analysis studio in the fracture processing data. Based on observations in the field, the geological structure contained in the study area is controlled by fracture. The type of fracture in the field is shear fracture. The results of the reconstruction of shear fracture in the study area is relatively northwest-southeast and north-south main direction.